2015
DOI: 10.1556/abiol.66.2015.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new SSR markers linked to leaf chlorophyll content, flag leaf senescence and cell membrane stability traits in wheat under water stressed condition

Abstract: Segregating F 4 families from the cross between drought sensitive (Yecora Rojo) and drought tolerant (Pavon 76) genotypes were made to identify SSR markers linked to leaf chlorophyll content, flag leaf senescence and cell membrane stability traits in wheat (Triticum aestivum L.) under water-stressed condition and to map quantitative trait locus (QTL) for the three physiological traits. The parents and 150 F 4 families were evaluated phenotypically for drought tolerance using two irrigation treatments (2500 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In wheat, QTLs controlling flag leaf-related traits have been identified on almost all 21 chromosomes [16,[29][30][31]. For example, using recombinant inbred line (RIL) population, 12 QTLs for chlorophyll content-related traits were mapped on chromosomes 1A, 3A, 3B, 3D, 4A, 5A, 6A, 6D, 7A and 7D [32]. Using different RIL populations, Yang et al [33] reported five additive QTLs for CC, among them, QChl-5A.1 was detected in multiple stages.…”
mentioning
confidence: 99%
“…In wheat, QTLs controlling flag leaf-related traits have been identified on almost all 21 chromosomes [16,[29][30][31]. For example, using recombinant inbred line (RIL) population, 12 QTLs for chlorophyll content-related traits were mapped on chromosomes 1A, 3A, 3B, 3D, 4A, 5A, 6A, 6D, 7A and 7D [32]. Using different RIL populations, Yang et al [33] reported five additive QTLs for CC, among them, QChl-5A.1 was detected in multiple stages.…”
mentioning
confidence: 99%
“…This leads to accelerated degradation of chlorophyll in photosynthetic organs such as leaves, reduced photosynthetic rate, and decreased photosynthetic efficiency ( Yang B. et al, 2016 ), hence lower fixation and assimilation of CO 2 ( Yang D. et al, 2016 ) leading to restricted dry matter accumulation and grain development ( Farooq et al, 2014 ). Therefore, the chlorophyll content in flag leaves is regarded as an indicator of drought resistance in wheat under drought stress ( Farooq et al, 2014 ; Barakat et al, 2015 ). Molecular studies on the genetic regulation of flag leaf chlorophyll content are therefore of considerable significance for maintaining and improving yield potential under drought stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the studies that have been reported involved different wheat populations and growth stages ( Zhang et al, 2009a ; Ilyas et al, 2014 ; Yu et al, 2014 ; Yang B. et al, 2016 ). The 82 reported QTLs controlling chlorophyll content were distributed across all 21 chromosomes ( Quarrie et al, 2006 ; Zhang et al, 2009a ; Zhang et al, 2009b ; Kumar et al, 2010 ; Vijayalakshmi et al, 2010 ; Ilyas et al, 2014 ; Saleh et al, 2014 ; Barakat et al, 2015 ; Li et al, 2015 ; Yang D. et al, 2016 ; Gupta et al, 2017 ; Shi et al, 2017 ; Yan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the genetic mechanism that regulates chlorophyll in wheat lags behind model crops such as rice ( Gupta et al., 2020 ). Under drought, high temperature, light intensity, and nutrient stress, QTL analysis of chlorophyll content has been performed ( Fang et al., 2004 ; Li et al., 2010 ; Vijayalakshmi et al., 2010 ; Christopher et al., 2018 ; Maulana et al., 2018 ; Kamal et al., 2019 ), and hundreds of QTLs were identified on 21 chromosomes of wheat ( Kumar et al., 2010 ; Li et al., 2010 ; Vijayalakshmi et al., 2010 ; Zhang et al., 2010 ; Kumar et al., 2012 ; Ilyas et al., 2014 ; Saleh et al., 2014 ; Barakat et al., 2015 ; Yang et al., 2016a ; Yang et al., 2016b ; Shi et al., 2017 ; Christopher et al., 2018 ; Puttamadanayaka et al., 2020 ; Yan et al., 2020 ; Yang et al., 2022 ). However, most studies used low-density SSR markers and were only identified in a few years/environments.…”
Section: Introductionmentioning
confidence: 99%